Studies on the Effect of Containers, Potting Mixtures and Growth Regulators on Growth and Survival of clove Seedlings - Prasannakumari Amma S (Department of Plantation Crops and Spices, College of Horticulture, 1981)
Studies were undertaken at the Instructional Farm , attached to the collage of Horticulture , Vellanikkara during 1979-80 to find out the methods to increase the percentage germination of clove seeds, to accelerate the rate of growth of the seedlings and to improve the percentage survival of the seedlings transplanted to the main field . The seeds collected during May ,June and July were classified as heavy , medium and light and sown with or without the pericarp . The seeds collected and sown during the month of June recorded the highest percentage of germination . However , the may seeds were superior with respect to rate of growth and vigour of the resultant seedling . Though heavy seeds recorded the highest percentage of germination , heavy and medium seeds were on par when the rate of growth of the seedlings was considered . The removel of pericarp increased the percentage germination , but did not influence the rate of growth of the resultant seedlings. G A at the concentrations ranging from 100 to 400ppm exhibited inhibitory effects on germination of clove seeds. The clove seedlings from the primary nursery when transplanted to improvised coconut husk pots filled with a mixture containing one part soil, one part sand and one part powered cowdung with bonemeal @ 2 teaspoons /pot and powered groundnut cake @2 teaspoons/pot, exhibited higher rate of growth . Sparying of GA 200ppm + urea 0.5 per cent to the clove seedlings transplanted to coconut husk pots or growing in one of the three potting mixtures tried , enhanced their rate of growth . Transferring the seedlings from the primary nursery to coconut husk pots at the second month and transplanting them to the mainfield with the container intact at the ninth month gave higher rate of survival.